2021
DOI: 10.4236/ojbd.2021.112007
|View full text |Cite
|
Sign up to set email alerts
|

Hematological and Biochemical Profile of Sickle Cell Patients in Critical and Inter-Critical Periods in Brazzaville, Republic of Congo

Abstract: Introduction: Sickle cell disease is a public health problem in the Republic of Congo where the prevalence of sickle cell trait is estimated at 1.25%. The objective of this study is to describe the variations of hematological and biochemical parameters of hemolysis in sickle cell patients in critical and inter-critical periods. Methods: This is a descriptive cross-sectional study including sickle cell patients followed regularly at the National Reference Center for Sickle Cell Disease (CNRDr) from November 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Also, Tolo A et al, 2006, Sekongo YM et al, 2015 each reported a sex-ratio of 1.3 in major sickle cell patients at the department of hematology of Yopougon teaching hospital and at the Abidjan blood transfusion center, respectively [8][9]. In contrast, Nanitelamio E et al, 2021 found a different sex-ratio of 0.9 in Congo Brazzaville in a similar study on hematological and biological profiles in sickle cell patients [10]. The average age was 17.9 ± 5.3 years and the extremes varied from 2 to 61 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Tolo A et al, 2006, Sekongo YM et al, 2015 each reported a sex-ratio of 1.3 in major sickle cell patients at the department of hematology of Yopougon teaching hospital and at the Abidjan blood transfusion center, respectively [8][9]. In contrast, Nanitelamio E et al, 2021 found a different sex-ratio of 0.9 in Congo Brazzaville in a similar study on hematological and biological profiles in sickle cell patients [10]. The average age was 17.9 ± 5.3 years and the extremes varied from 2 to 61 years.…”
Section: Discussionmentioning
confidence: 99%
“…The median of hemoglobin (Hb) level was significantly lower in SSFA2 subjects compared to SAFA2 subjects: 7 g/dL [IQR = 7] versus 10g/dL [IQR = 8], p < 0.001. Several studies have found a significant difference between the Hb levels of the homozygous subject compared to other forms of sickle cell disease in the steady-state, thus demonstrating greater chronic hemolysis in homozygous subjects [10][11][12][13]. Hyper IB was frequent in young subjects.…”
Section: Discussionmentioning
confidence: 99%